2012
DOI: 10.1590/s1516-14392012005000066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of impact strength of polyamide 6/bentonite clay nanocomposites

Abstract: Nanocomposites of polymer/clay have had much attention in recent years, particularly those developed with layered silicates due to the need of engineering materials more efficient than pure polymers for certain applications. The level of exfoliation of layered silicates in crystalline structure of polymer matrices has been studied and has been observed that it affects the crystalline behavior and the physical and mechanical properties. In this study, nanocomposites of polyamide 6 were obtained by the melt inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Polyamides are semicrystalline polymers and the presence of peak broadening indicates the existence of amorphous regions. Furthermore, the introduction of clay, regardless of the amount, changes slightly the shape and intensity of the peaks at 20º and 24º of the polyamide6 [30][31][32][33][34][35] . It was found that the addition of 5% w/w of MMT in PA6, cause the appearance of the new reflection at 2θ = From Figure 2, it is noted that the general profile of FTIR spectra of the PA6 remained virtually unchanged, except for a small increase in the intensity of the peaks at wavelengths of 800, 1033 and 1095 cm -1 .…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 94%
See 1 more Smart Citation
“…Polyamides are semicrystalline polymers and the presence of peak broadening indicates the existence of amorphous regions. Furthermore, the introduction of clay, regardless of the amount, changes slightly the shape and intensity of the peaks at 20º and 24º of the polyamide6 [30][31][32][33][34][35] . It was found that the addition of 5% w/w of MMT in PA6, cause the appearance of the new reflection at 2θ = From Figure 2, it is noted that the general profile of FTIR spectra of the PA6 remained virtually unchanged, except for a small increase in the intensity of the peaks at wavelengths of 800, 1033 and 1095 cm -1 .…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 94%
“…Probably, the presence of the clay crystalline behavior altered of PA6. However, when small percentages of clay are added to polymer matrices, the degree of crystallinity Xc, increases the nanocomposite which may demonstrate a nucleating effect of the clay 34,35,49 . The SEM images of the top surface and cross section of pure PA6 membranes and their hybrids 1, 3, 5% w/w of MMT, adding 10% w/w CaCl 2 , are shown in figures from 3 to 6.…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 99%
“…The mixture was stirred for more 20 minutes. After 24 h the mixture of bentonite and the salt were washed with distilled water for several times to remove the salt excess and it was dried at 60°C for 48 h, and finally, passed in a sieve 200 mesh detailing of the procedure is described by Díaz [22,23] and others authors [8,11,15,24] . In the nanocomposite preparation, before any processing step, all the materials with PA6 were dried in an oven with circulating air at 80°C for 1 h. Afterwards, these materials were kept in an oven under vacuum at 80°C for 24 h. The nanocomposites were prepared by two steps.…”
Section: Methodsmentioning
confidence: 99%
“…From the 60s, the literature began to report the development of the first polymer/clay nanocomposites. From then until the present day, much attention has been given to polymer nanocomposites, especially those developed with layered silicates, due to the great need of modern materials of engineering and the fact that the pure polymers do not present the behavior or the properties required for certain application [3][4][5][6][7][8][9][10][11][12][13][14][15] . Organic/inorganic hybrids exhibit improved properties compared to the pure polymers or conventional composites, such as higher elastic modulus and tensile strength, higher resistance to solvents and flame resistance and good optical, magnetic and electric properties [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation